Origin of Nontreponemal Antibodies During Treponema pallidum Infection: Evidence From a Rabbit Model. (21st April 2018) - Gao, Kun; Shen, Xu; Lin, Yong; Zhu, Xiao-Zhen; Lin, Li-Rong; Tong, Man-Li; Xiao, Yao; Zhang, Hui-Lin; Liang, Xian-Ming; Niu, Jian-Jun; Liu, Li-Li; Yang, Tian-Ci
Abstract : Treponema pallidum contains a cardiolipin antigen with weak immunogenicity and can elicit the production of a low-titer nontreponemal antibody. The damaged host–cell cardiolipin antigen may play an imperative role in inducing high nontreponemal antibody production during syphilis infection. Abstract: The origin of nontreponemal antibodies during syphilis infection is hotly debated. Here, we analyzed the immune response in rabbits immunized with various antigens. Inactivated treponemes elicited the production of low-titer nontreponemal antibodies in some rabbits. Cardiolipin combined with bovine serum albumin also induced anticardiolipin antibody production. These findings indicate that Treponema pallidum contained a cardiolipin antigen with weak immunogenicity. However, active T. pallidum induced higher nontreponemal antibody production with strong immunogenicity at an earlier time point, and the antibody titer was consecutive, suggesting the high nontreponemal antibody titer resulted from the combined effects of both the T. pallidum cardiolipin antigen and the damaged host–cell cardiolipin antigen during syphilis infection, the latter of which plays a major role in the induction of nontreponemal antibody production. Our study provides direct animal evidence of the origin of nontreponemal antibodies during T. pallidum infection.